Unknown crusader castles - Molin, Kristian (Hambledon and London, 2001)
The capture of Jerusalem by the "First Crusade" in 1099 heralded the beginning of an armed struggle in Palestine. It was a war dominated by the building, securing and besieging of castles. This work covers the military history of the crusades and investigates the role of a wide range of castles.